Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 11 - 11.3 - Geometric Sequences and Series - 11.3 Exercises - Page 796: 71



Work Step by Step

$\displaystyle \sum_{n=0}^{∞}(-\frac{1}{2})^n=(-\frac{1}{2})^0+(-\frac{1}{2})^1+(-\frac{1}{2})^2+...$ $a_1=(-\frac{1}{2})^0=1$ $r=\frac{a_2}{a_1}=\frac{(-\frac{1}{2})^1}{(-\frac{1}{2})^0}=-\frac{1}{2}$ $S=\frac{a_1}{1-r}=\frac{1}{1-(-\frac{1}{2})}=\frac{1}{\frac{3}{2}}=\frac{2}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.